Legal Protection for Victims of Crime Criminal Fraud Through Social Media - Yusuf, Auliya; Zainuddin, Zainuddin; Rustam, Rustam (Faculty of Law, Universitas Muslim Indonesia, 2025)
This research aims to analyze the form of legal protection provided to victims. This research also identifies the obstacles faced in implementing legal protection for victims and offers solutions that can be implemented to overcome these obstacles in the process of investigating criminal acts of fraud on social media. This research uses empirical methods that have descriptive and prescriptive qualitative characteristics. Data was obtained through interviews and data collection with law enforcement officials. The process of investigating criminal acts of fraudulent buying and selling transactions on social media in Enrekang is still ineffective. Due to several obstacles that hinder the legal process against perpetrators of criminal acts of fraudulent buying and selling transactions. The recommendations of this research are important so that police investigators and the community can work together better to speed up the investigation process until the determination of the suspect.